(untitled) (LEARNing Landscapes, 2022)
How can comedy be used as an effective tool and truly help innovate the learning experience? This paper outlines how aspects of comedy have been creatively integrated into primary and secondary academic curricula such as English Language Arts, social studies, drama, as well as in areas of mental health and wellness. The essay demonstrates, for example, how participating in stand-up performances helped sharpen students’ critical thinking abilities and presentation skills. It also underscores comedy’s pedagogical utility and versatility, its value in the classroom, and its promising potential as a stand-alone option in the domain of arts education.